Introduction - Szulakiewicz, Władysława; Bieś, Andrzej Paweł (Studia Paedagogica Ignatiana, 2022)
The present volume of the journal Studia Paedagogica Ignatiana is dedicated to the problems of the history of education in Poland in the 20th century, presented from the perspective of its founders. Although the presented texts do not cover many issues related to the history of education in Poland of that period, they may be seen as an invitation for further research on this topic.